2017
DOI: 10.1080/13697137.2017.1395410
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between 25(OH)D concentration, sarcopenia and HOMA-IR in postmenopausal Korean women

Abstract: Sarcopenia was associated with both insulin resistance and 25-hydroxyvitamin D concentration in postmenopausal Korean women, regardless of obesity status. However, 25-hydroxyvitamin D concentration was not associated with insulin resistance. Sarcopenia is therefore of greater clinical importance due to its close relationship with insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Vitamin D deficiency in cancer survivors impacts body composition, increasing the risk for both bone loss and even sarcopenia (97,102). Vitamin D levels are inversely correlated with sarcopenia in older adults, and vitamin D supplementation is now considered a possible treatment for improving muscle function in the elderly (103)(104)(105). The mechanism by which vitamin D improves physical function may be related to anti-inflammatory properties, through local production of the hormone calcitriol, the active metabolite of vitamin D 3 (101,106).…”
Section: Micronutrientsmentioning
confidence: 99%
“…Vitamin D deficiency in cancer survivors impacts body composition, increasing the risk for both bone loss and even sarcopenia (97,102). Vitamin D levels are inversely correlated with sarcopenia in older adults, and vitamin D supplementation is now considered a possible treatment for improving muscle function in the elderly (103)(104)(105). The mechanism by which vitamin D improves physical function may be related to anti-inflammatory properties, through local production of the hormone calcitriol, the active metabolite of vitamin D 3 (101,106).…”
Section: Micronutrientsmentioning
confidence: 99%
“…Some researchers found insulin resistance inversely correlated with bone mineral density while other studies found insulin resistance causing smaller bone size and greater bone mineral density [23,48]. Insulin resistance and lower 25(OH)D levels in postmenopausal women also leads to muscle attenuation and sarcopenia [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…The effect was more significant for participants with low 25(OH)D concentration (<30 nmol/L) and for older participants (≥65 years). In addition, a cross-sectional study based on data from the South Korea National Health and Nutrition Examination Survey with postmenopausal Korean women showed that higher 25(OH)D concentration was associated with lower risk of sarcopenia [ 65 ].…”
Section: Role Of Nutrition In Healthy Ageing In Asiamentioning
confidence: 99%